1996
DOI: 10.1021/jm950893j
|View full text |Cite
|
Sign up to set email alerts
|

The Squalestatins:  Inhibitors of Squalene Synthase. Enzyme Inhibitory Activities and in Vivo Evaluation of C3-Modified Analogues

Abstract: Squalestatin analogues modified at C3 were prepared and evaluated for their ability to inhibit rat liver microsomal squalene synthase in vitro. While the 4,6-dimethyloctenoate ester group at C6 was maintained, a number of modifications to the C3 carboxylic acid were well tolerated. However, in the absence of the C6 ester group, similar modifications to the C3 carboxyl group caused loss of activity. Selected compounds were evaluated for their ability to inhibit cholesterol biosynthesis in vivo in rats 1 and 6 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Squalestatin, GR 105155X, belongs to a group of complex fungal metabolites named squalestatins by Glaxo and zaragosic acids by Merck (21). Squalestatins inhibit squalene synthase activity at nanomolar concentrations and display broad-spectrum antifungal activity (21), but even at 100 g/ml GR 105155X had no effect on P. carinii viability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Squalestatin, GR 105155X, belongs to a group of complex fungal metabolites named squalestatins by Glaxo and zaragosic acids by Merck (21). Squalestatins inhibit squalene synthase activity at nanomolar concentrations and display broad-spectrum antifungal activity (21), but even at 100 g/ml GR 105155X had no effect on P. carinii viability.…”
Section: Discussionmentioning
confidence: 99%
“…Squalestatin, GR 105155X, belongs to a group of complex fungal metabolites named squalestatins by Glaxo and zaragosic acids by Merck (21). Squalestatins inhibit squalene synthase activity at nanomolar concentrations and display broad-spectrum antifungal activity (21), but even at 100 g/ml GR 105155X had no effect on P. carinii viability. There are now a number of squalestatin and zaragosic acid derivatives, and it is known that compounds with similar enzymeinhibitory activities can have very different effects in lowering sterol biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The polyacidic charge of the bicyclic core elicits strong binding and inhibitory activity against human SQS, accompanied by more extensive hydrogen bonds than those found from other inhibitors bearing carboxylic or phosphonic acid groups (23,31). Various degrees of substitutions along the C-3, C-4, and C-5 in rat liver microsomal SQS and in vivo models have been discussed (9,(33)(34)(35).…”
Section: Resultsmentioning
confidence: 99%
“…More than a half of commercialized drugs are natural product-based compounds. As ZAs exhibit fascinating biological activity for SQS, much work has focused on total synthesis by Merck, Glaxo, and other groups in an attempt to identify the key structural features of SQS-inhibitory activity (9,20,21,(33)(34)(35)(36)(37). However, variations of C-3, C-4, and C-5 tricarboxylic acids, C-4, C-7 dihydroxyl groups, and the C-1 and C-6 mimetics are often at odds with regard to which structural changes make the compounds more active or less.…”
Section: Discussionmentioning
confidence: 99%
“…Compound 3, a completely synthetic derivative that eliminates both carboxyls and the hydroxyl on C3 and C4 exhibited only weak activity (IC 50 = 1.1 µM) [106]. The group at Glaxo also demonstrated that more significant changes were tolerated at the C3-position [9]. Compounds in which the C3-carboxyl (CO 2 H) of squalestatin S1 was replaced with CH 2 OH, COCH 3 , CH 2 OCH 3 , CH 2 NH 2 , CH 2 N(CH 3 ) 2 , or CH 2 NHCONH 2 maintained in vitro potency (IC 50 = 3 -15 nM) but possessed shorter in vivo durations of action.…”
Section: Zaragozic Acids/squalestatinsmentioning
confidence: 99%